Analysis of oxygen shell splitting in hydrothermally grown single crystal ThO2(200). Issue 11 (12th October 2015) - Kelly, T. D.; Petrosky, J. C.; McClory1, J. W.; Mann, J. M.; Kolis, J. W.
Abstract : Single crystals of ThO2 have been synthesized using hydrothermal growth and studied using the X‐ray absorption fine structure (XAFS) technique. The extended X‐ray absorption fine structure (EXAFS) has been extracted from the XAFS and analyzed using a novel, computational Latin hypercube sampling method. The methodology not only confirms the expected space group and crystal structure, it also identifies the origin of a previously reported split O shell. Since EXAFS is a local order analysis technique, the O shell splitting is identified as an O atom occupying an interstitial site. This result is significant for examining O 2– transport in a ThO2 matrix and corroborating research indicating partial Th 5f occupancy that is similar to hyper‐stoichiometric UO2+ x compounds. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : Extended X‐ray photoemission fine structure data of hydrothermally synthesized ThO2 has been interpreted. The data analysis included developing a novel Latin hypercube analysis tool used to identify a point defect structure, agreeing with recent experimental and theoretical research. Results are important to the understanding of the subtle role of 5f electrons in ThO2 influencing O migration applications (e.g. solid state electrolytes) and future studies of mixed Th x U y O2 oxide fuel stabilization.